Protocol for the ADDITION-Plus study: a randomised controlled trial of an individually-tailored behaviour change intervention among people with recently diagnosed type 2 diabetes under intensive UK general practice care. - Griffin, S; Simmons, R; Williams, K; Prevost, A; Hardeman, W; Grant, J; Whittle, F; Boase, S; Hobbis, I; Brage, S; Westgate, K; Fanshawe, T; et al. (BioMed Central, 2011)
BACKGROUND: The increasing prevalence of type 2 diabetes poses both clinical and public health challenges. Cost-effective approaches to prevent progression of the disease in primary care are needed. Evidence suggests that intensive multifactorial interventions including medication and behaviour change can significantly reduce cardiovascular morbidity and mortality among patients with established type 2 diabetes, and that patient education in self-management can improve short-term outcomes. However, existing studies cannot isolate the effects of behavioural interventions promoting self-care from other aspects of intensive primary care management. The ADDITION-Plus trial was designed to address these issues among recently diagnosed patients in primary care over one year. METHODS/DESIGN: ADDITION-Plus is an explanatory randomised controlled trial of a facilitator-led, theory-based behaviour change intervention tailored to individuals with recently diagnosed type 2 diabetes. 34 practices in the East Anglia region participated. 478 patients with diabetes were individually randomised to receive (i) intensive treatment alone (n = 239), or (ii) intensive treatment plus the facilitator-led individual behaviour change intervention (n = 239). Facilitators taught patients key skills to facilitate change and maintenance of key behaviours (physical activity, dietary change, medication adherence and smoking), including goal setting, action planning, self-monitoring and building habits. The intervention was delivered over one year at the participant's surgery and included a one-hour introductory meeting followed by six 30-minute meetings and four brief telephone calls. Primary endpoints are physical activity energy expenditure (assessed by individually calibrated heart rate monitoring and movement sensing), change in objectively measured dietary intake (plasma vitamin C), medication adherence (plasma drug levels), and smoking status (plasma cotinine levels) at one year. We will undertake an intention-to-treat analysis of the effect of the intervention on these measures, an assessment of cost-effectiveness, and analyse predictors of behaviour change in the cohort. DISCUSSION: The ADDITION-Plus trial will establish the medium-term effectiveness and cost-effectiveness of adding an externally facilitated intervention tailored to support change in multiple behaviours among intensively-treated individuals with recently diagnosed type 2 diabetes in primary care. Results will inform policy recommendations concerning the management of patients early in the course of diabetes. Findings will also improve understanding of the factors influencing change in multiple behaviours, and their association with health outcomes.